The Initiation of healthy villages with tourism potential through the cultivation of oyster mushrooms with immunomodulatory properties - Ana Mardiyaningsih; Hery Setiyawan; Wika Rinawati (Community Empowerment, 2022)
The Women Farmers Group at Padukuhan Gowok is a farmer group that can play a strategic role in strengthening the community's health and economy through oyster mushroom cultivation. Oyster mushrooms are only known to the general public as a common food ingredient; they are unknown for their immune-boosting capabilities. Mushroom production also often experiences crop failure due to lack of knowledge, environmental conditions in kumbung which are still affected by climate and weather, as well as pest disturbances in the form of insects that attack beglogs, resulting in low production capacity. The educational program for KWT Lestari members has the potential to raise knowledge by 31 points (or 56%) about the morphology and nature of mushroom growth and by 25 points (or 89%) about the health advantages of mushrooms. Oyster mushroom cultivation assistance is carried out through training and repair of kumbung facilities through renovation and installation of sprayers, but has not been able to increase production capacity. The initiation of the potential for mushroom picking tourism has been carried out by making a kumbung and mushroom cafe design as well as accepting the first visit of mushroom picking tourism.